El sufijo -nte del verbo ser en español - Ferrell Ramírez, Marco Aurelio (2024)
In the conjugation tables of verbs in Spanish, the non-personal forms that are shown, taking amar as an example, are the infinitive (to sing, basic form of the verb), the gerund (singing, adverbial form) and the participle (sung, adjective). Related to this, we have in Spanish a derived element ending in -nte that can function either as a noun or as an adjective--cantante. In this paper, the existence and survival of the form in -nte of the Spanish verb ser (‘to be’) as a cultured word will be demonstrated, and it will be pointed out what the deverbal adjective with suffix -nte that corresponds to said verb is. Bibliographic research has been carried out and databases of the Royal Spanish Academy were consulted; and due to the nature of the object of study, a grammatical analysis of the element studied was conducted. In terms of results, a total of 39 occurrences of the word with the suffix -nte were found, of which 24 are shown in the article. In the conclusions, it is established that the derivative of being ending in -nte —which is present in the cultured speech— occurs from the 13th century to the present day.